Teoria do agir comunicativo e meios adequados de resolução do conflito: uma avaliação dos centros judiciários de solução de conflito e cidadania do Tribunal de Justiça do Estado do Maranhão na perspectiva do Jurisdicionado - CASTRO, Maíra Lopes de (2019)
The paper proposes to evaluate the Judicial Centers for Conflict Resolution and Citizenship of the Court of Justice of the State of Maranhão, in light of the theory of Communicative Action of the philosopher Jurgen Habermas. In this sense the central questions of the research developed here are: to what extent does the institutionalization of adequate means of conflict resolution within the scope of the Judiciary approximates Jurgen Habermas's Theory of Communicative Action, propitiating the reconstruction of democratic ties between society and Judicial power? And, in a subsidiary way: in what way does the rationality applied by public policy allow greater participation and recognition of the jurisdiction in the delimitation of its demands? To do so, in its first chapter, it faces the facets of the crisis experienced by the Judiciary, looking to re-signify the concept of access to justice, adopting the perspective of access to justice as access to the just legal order. Then, in chapter two, the structure of the National Judicial Policy is presented as an adequate treatment of conflicts of interest, in order to highlight the proximity and distances between the Habermas communicative action and the National Judicial Policy for the adequate treatment of conflicts. In methodological terms, the research is classified as bibliographic, deductive, exploratory and descriptive. As for the technical procedures, it is classified as a field study, and a fully structured interview technique was applied to the users of the 1st Judicial Center for Conflict Resolution and Citizenship of the Court of Justice of the State of Maranhão, in order to gauge their perception about the service provided by the Judiciary. Lastly, the content analysis method was used to analyze the legislative micro-system that guides the implementation of the National Judicial Policy for the adequate treatment of conflicts: Resolution 125/2010 of the National Council of Justice, Law 13.105 / 2015 (Code of Brazilian Civil Procedure) and Law 13.140 / 2015 (Mediation Law), in order to identify the elements "not said" by the legislation.